Reduction of the Diazo Functionality of α-Diazocarbonyl Compounds into a Methylene Group by NH3BH3 or NaBH4 Catalyzed by Au Nanoparticles - Marios Kidonakis; Manolis Stratakis (Nanomaterials, 2021)
Supported Au nanoparticles on TiO2 (1 mol%) are capable of catalyzing the reduction of the carbene-like diazo functionality of α-diazocarbonyl compounds into a methylene group [C=(N2) → CH2] by NH3BH3 or NaBH4 in methanol as solvent. The Au-catalyzed reduction that occurs within a few minutes at room temperature formally requires one hydride equivalent (B-H) and one proton that originates from the protic solvent. This pathway is in contrast to the Pt/CeO2-catalyzed reaction of α-diazocarbonyl compounds with NH3BH3 in methanol, which leads to the corresponding hydrazones instead. Under our stoichiometric Au-catalyzed reaction conditions, the ketone-type carbonyls remain intact, which is in contrast to the uncatalyzed conditions where they are selectively reduced by the boron hydride reagent. It is proposed that the transformation occurs via the formation of chemisorbed carbenes on Au nanoparticles, having proximally activated the boron hydride reagent. This protocol is the first general example of catalytic transfer hydrogenation of the carbene-like α -ketodiazo functionality.